DEVELOPMENT OF INTELLECTUAL CAPITAL IN THE ERA OF DIGITALIZATION IN THE CONTEXT OF INCREASING COMPETITIVENESS INDUSTRIAL ENTERPRISES OF UKRAINE - Nahorniak, H.S.; Hanouff, K.E. (The actual problems of regional economy development, 2023)
The article is devoted to the problems of the development of intellectual capital (IC) in the era of digitalization of the global space in order to increase the competitiveness of industrial enterprises. The purpose of the study is the need to create effective mechanisms to ensure the formation and development and use of intellectual capital in the context of digital transformation as a basis for increasing the competitive advantages of the country's industrial enterprises. This determines the necessity and relevance of further scientific research in the field of developing adaptive theoretical and methodological approaches and practical recommendations that allow to effectively organize the development of intellectual capital at industrial enterprises in the conditions of the formation of a digital environment. Research methods are historical and empirical methods, the method of scientific abstraction, methods of analysis and synthesis, and the method of systematic analysis. The scientific novelty consists in the development of a complex and holistic approach to ensuring the transformation of the intellectual capital of industrial enterprises due to synthesis with digital technologies, the use of which would allow to accelerate the development of industrial enterprises, the country's market economy and its acceleration in entering the developed global space. The study examines the possibilities of developing the intellectual capital of industrial enterprises, in which their transformed human capital in combination with digitalization processes is key as a significant source of increasing the competitiveness of industrial enterprises. It was determined that the creative labor energy of an intellectual worker and the system of creative latest knowledge are human capital, which together with structural and consumer capital is intellectual capital, which ultimately ensures the reproduction of economic innovations of all forms and types at different hierarchies and levels of management as the state and enterprises. It is summarized that the task of developing and strengthening the competitiveness of intellectual capital due to synthesis with digital knowledge, tools, skills and abilities will contribute to the improvement of the quality of intellectual capital and is an integral and integral part of the task of increasing the competitiveness of the country's industrial enterprises. In the study, the authors clarified and specified the methodological perspective or disciplinary matrix of the study of knowledge management methods in the modern economy, revealed the features of corporate knowledge management, which are determined by the system integration approach to the maintenance and development of human capital of a modern industrial enterprise in the digital space. The practical significance of the research lies in the possibility of using the proposed mechanisms to ensure the effectiveness of the formation, development and use of intellectual capital with implemented digital knowledge in increasing the efficiency of industrial enterprises and the formation of competitive advantages.